Українці в Березі Картузькій у 1934 р.: чисельність та режим утримання - Разиграєв, О. (Краєзнавство, 2018)
Стаття присвячена перебуванню українців у, створеному в 1934 р. на теренах Поліського воєводства Польської держави, таборі «Береза Картузька». Цей заклад було утворено з метою нейтралізації та залякування як опозиційних до офіційної влади політичних сил, так і окремих осіб. Значну частину в'язнів досліджуваного карального закладу становили українці, які почали прибувати в Березу Картузьку вже в першій половині липня 1934 р. Це були члени ОУН, її симпатики, а також патріотично налаштовані особи. В'язні-українці становили в таборі окрему групу, члени якої характеризувались належним рівнем освіти та високою національною свідомістю. Береза Картузька не виконала тих завдань, які покладались на неї властями. Більшість українських націоналістів після звільнення повертались до антипольської діяльності. Водночас, табір став одним із символів авторитарного режиму Польщі 1930-х років. The article is devoted to the presence of Ukrainians in the camp in the Bereza Kartuska, created in 1934 in the Polesie Voivodship of the Polish. It was located in the former Russian imperial military barracks. This institution was formed to neutralize and intimidate political forces and individuals as opposition to the official authority. The prisoners were held there not by the court decision, but according to the will of the representatives of the state administration. In addition, prisoners were subjected to psychological and physical suffering, forced into work. The funds allocated by the state for the maintenance of prisoners in other penitential institutions of Poland were higher than intended for persons who were in Bereza Kartuska. The food for the prisoners was extremely poor. Creation of a camp in the Bereza Kartuska caused a sharp critique of part of society, including the Polish politics. A significant proportion of the prisoners of the investigated criminal institution were Ukrainians, who began to arrive in the Bereza Kartuska in the first half of July 1934. They were members of the OUN, its sympathizers and patriotic-minded people. Ukrainian prisoners were a separate group in the camp, whose members were characterized by a proper level of education and a high national consciousness. Among the prisoners of the “ukrainian group” who were in the Bereza Kartuska in 1934, it is possible to distinguish: R. Shukhevych, T. Borovets, D. Grytsay, Y. Starukh, V. Timchii, V. Vavruk, G. Klymiv, V. Fedak, V. Ohrimovych, D. Valko, M. Goloyad, Y. Gorobovy, O. Kuts, R. Lopachak, M. Laska, D. Nikita, I. Mitring, M. Opryshko, J. Pavlyshyn, F. Panas, M. Paraponiak, V. Baran, A. Danchevsky, G. Demchina, I. Krysko, V. Rogovsky, and others. Bereza Kartuska did not fulfill the tasks relied on it by authorities. Most Ukrainian nationalists returned to anti-Polish activities after release. At the same time, the camp became one of the symbols of the authoritarian regime of Poland 1930s.